Urban ground engineering proceedings of the international conference organized by the Institution of Civil Engineers and held in Hong Kong, China, on 11-12 November 1998 - Clarke, B. G. 1950- (Thomas Telford, 1999)
These conference proceedings address the wide range of geotechnical issues associated with urban development, from the use of case histories and reviewing existing data to the techniques and procedures associated with new construction works.